2007
DOI: 10.1080/00102200600808722
|View full text |Cite
|
Sign up to set email alerts
|

Flame Surface Densities in Premixed Combustion at Medium to High Turbulence Intensities

Abstract: The surface densities of flame fronts in turbulent premixed propane= air flames were determined experimentally. The instantaneous flame fronts were visualized using laser induced fluorescence (LIF) of OH on two Bunsen type burners of 11.2 and 22.4 mm diameters. Nondimensional turbulence intensity, u 0 =S L , was varied from 0.84 to 15, and the Reynolds number, based on the integral length scale, varied from 34 to 467. These flames are in the flamelet combustion regime as defined by the most recent turbulent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…In addition, it can be seen from the Fig.7 the maximum flame area density does not change with the increase in turbulence intensity. This result is consistent with those found by (Gülder and Smallwood 2007), who studied the flame area density in a premixed turbulent flame at a vast level of turbulence intensity in a Bunsen burner and concluded that the maximum flame surface density does not vary with turbulence intensity.…”
Section: Flame Area Densitysupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, it can be seen from the Fig.7 the maximum flame area density does not change with the increase in turbulence intensity. This result is consistent with those found by (Gülder and Smallwood 2007), who studied the flame area density in a premixed turbulent flame at a vast level of turbulence intensity in a Bunsen burner and concluded that the maximum flame surface density does not vary with turbulence intensity.…”
Section: Flame Area Densitysupporting
confidence: 82%
“…(Gülder and Smallwood 2007) studied the flame area density in a premixed turbulent flame at the vast level of turbulence intensities and found that turbulence affects the flame area density. In addition, the maximum flame surface density does not vary with the turbulence intensity.…”
Section: Introductionmentioning
confidence: 99%
“…This may result in an increase in the turbulent burning velocity due to an increase in flame surface wrinkling. This hypothesis is supported by the experimental data showing that the turbulent burning velocity increases with increasing bulk flow velocity, see, e.g., [4,13,14]. However, the observed trend may not be solely due to the effect of bulk flow velocity since the total turbulence intensity increases simultaneously with the bulk flow velocity in these experiments.…”
Section: Introductionmentioning
confidence: 50%
“…12 Flame-front segments (white) of sample image in Fig. 6 Shepherd and Cheng 2001;Haq et al 2002;Gülder and Smallwood 2007;Petersson et al 2007;Kiefer et al 2008). This technique has also been applied to flows seeded with either oil droplets (Shepherd et al 1992;Veynante et al 1994;Shepherd 1996) or solid particles (Pfadler et al 2005;Pfadler et al 2007) where planar imaging is used to determine the reactant region and hence the flame-front.…”
Section: Filter Comparisonmentioning
confidence: 98%